A case report of gastric cancer with brain metastasis - Saini, Rohit; Kumar, Ritesh; Yadav, Ravind; Yadav, Rahul Kumar; Singh, Pritanjali; Majhi, Sushmita (Indian Journal of Case Reports, 2025)
It’s rare for gastric cancer to present with brain metastasis. A case of gastric cancer with multiple brain metastases is described in the current investigation. To the best of our knowledge, there are very few reports of brain metastasis from gastric cancer. In April 2021, a 48-year-old man presented with complaints of abdominal pain, headache, lack of appetite, and weight loss history. Diagnosed as a case of moderately differentiated, Her2 neu negative gastric cancer with liver and brain metastasis after workup. Brain metastasis was confirmed through contrast-enhanced magnetic resonance imaging. The patient was treated with palliative fluorouracil, oxaliplatin, and docetaxel regimen of chemotherapy and whole-brain radiation at a total dose of 30 gray in 10 fractions. The patient survived for the next 19 months. According to this case study, gastric cancer may present with a brain metastasis and survival of those patients can be increased if given the advantage of radiotherapy and palliative chemotherapy.